Analysis of Water Hyacinth Processing for Handicrafts by the Community in Samosir Regency: Analisis Pengolahan Eceng Gondok untuk Kerajinan Tangan oleh Masyarakat di Kab.Samosir - Nainggolan, Monika (Universitas Negeri Surabaya, 2023)
This research has a background on the importance of literacy education in cultivating and developing reading, writing, arithmetic and language skills as an effort to improve the quality of life. This study aims to determine whether the use of audio-visual media can improve early literacy skills in early childhood in the Sukaraja Environment, Medan City. The research method in this research is descriptive research method. The author takes the location, namely in Medan Maimun District, Medan City. This study uses a qualitative approach. Based on the findings obtained from observations made and also interviews with several respondents, it was stated that early literacy in children was still lacking and interest in learning from children was still relatively low. Then in this study the learning process was carried out using audiovisual media to analyze whether the use of media would affect children's abilities. From the results of the activity it can also be concluded that learning media is important for the learning process, creative learning media will generate high interest in learning and from this interest, the learning process can be said to be perfect when the participation of enthusiastic learning citizens in the process and knowledge of students can be trained and focused on learning materials